2016
DOI: 10.1002/ccd.26575
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of mitral valve annulus plane and circumflex‐right coronary artery plane: Implications for transcatheter mitral valve implantation

Abstract: LCX-RCA plane has a close and consistent relationship to the MAP and can be useful to guide TMVI. Accurate imaging of mitral valve annular plane during TMVI procedure is challenging. MAP guided by fluoroscopy might be crucial to guide successful prosthesis deployment. A plane defined by the left circumflex- right coronary arteries in the atrioventricular grove has a consistent relationship with MAP; this can be used aided by pre-procedural MDCT to guide TMVI procedure. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In one study of MDCT analysis of the LCx relation to the mitral annulus, the proximal LCx can be remarkably close to mitral annulus in mid systole. Another study suggests that LCx place can be used as a marker to locate the mitral annulus plane during the procedure, with distance of <5 mm between the two planes (83)(84)(85)(86)(87). In TMVR studies, there was no LCx injury or occlusion reported, and rather it seems a complication of transcatheter annuloplasty.…”
Section: Left Circumflex Coronary Artery Occlusionmentioning
confidence: 99%
“…In one study of MDCT analysis of the LCx relation to the mitral annulus, the proximal LCx can be remarkably close to mitral annulus in mid systole. Another study suggests that LCx place can be used as a marker to locate the mitral annulus plane during the procedure, with distance of <5 mm between the two planes (83)(84)(85)(86)(87). In TMVR studies, there was no LCx injury or occlusion reported, and rather it seems a complication of transcatheter annuloplasty.…”
Section: Left Circumflex Coronary Artery Occlusionmentioning
confidence: 99%
“…Lifelike, 4DCT cinematic rendering may be more useful compared to traditional 3D volumetric reconstructions. CT is indispensable for mitral annulus sizing and for the prediction and evaluation of LVOT obstruction risk in TMVR ( Figure 3, Video 2) (10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Additionally, CT allows precise measurement of the geometric mitral valve area, predicts optimal fluoroscopic angles and identifies the location of the coronary sinus in relation with the annulus (Figure 4).…”
Section: Mitral Valve Imaging-multimodality Approachmentioning
confidence: 99%